The absorbent mind - Montessori, Maria, 1870-1952. ([Minooka, IL?] : BN Pub., 2012)
A leading educator discusses the importance of the first six years to a child's normal physical and emotional development.
The child and the world reconstructed -- Education for life -- The periods of growth -- A new orientation -- The miracle of creation -- One plan, one method -- Man's universality -- The psycho-embryonic life -- The conquest of independence -- Care to be taken at life's beginnning -- On language -- The call of language -- Obstacles and their consequences -- Movement and total development -- Intelligence and the hand -- Development and imitation -- From unconscious creator to conscious worker -- The new teacher -- Further elaboration through culture and imagination -- Character and its defects in young children -- A social contribution of the child : normalization -- Character-building a conquest, not a defense -- The sublimation of possessiveness -- Social development -- Society by cohesion -- Error and its control -- The three degrees of obedience -- The Montessori teacher -- The fountain source of love the child.
Previously published: New York : Holt, Rinehart, and Winston, 1967.
Includes bibliographical references.
Translation of: La mente del bambino.
Keywords: Child psychology; Educational psychology